MENINGKATKAN PRODUKSI PADI SAWAH DENGAN PUPUK ORGANIK PELEPAH SAWIT (PUPUK POPS); EVALUASI MUSIM TANAM KE-TIGA - Sunarti Sunarti; Ikhsan Hasibuan; Sarina Sarina (University of Prof. Dr. Hazairin, SH, 2018)
The availability of farm inputs which can be gotten easily, cheaply at anytime is one of important keys to successful of organik agriculture practice. Organik fertilizer which is made of fronds of oil palm, or we call it POPS fertilizer, is an alternative fertilizer that fulfill that expectation. There are at least four advantages of using fronds as source of organik fertilizer are available in abundant amounts, very cheap or even free, as product product and could be chop by using chopper machine. A research had been done in irrigated wetland field located in Padang Rambun village in Seluma District, Bengkulu Province from January to May 2018. A split plot design was used to analyze three kinds of fertilizers were POPS, cow manure bokashi and anorganik fertilizers and three levels of nitrogen dosages were 120, 90 and 60 kg/ha. The results showed that POPS fertilizer gave the best rice performances on height, number of tillers, number of productive tillers and yield (6.81 ton/ha). In addition, the highest dosage provided best yield by 6.69 ton/ha. Finally, the rice productivity has consistently increased since the first year of POPS fertilizer application.